2021
DOI: 10.1136/tobaccocontrol-2020-056259
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of menthol cigarette bans on cessation and smoking behaviours in Canada: longitudinal findings from the Canadian arm of the 2016–2018 ITC Four Country Smoking and Vaping Surveys

Abstract: ObjectiveTo evaluate the impact of menthol cigarette bans in seven Canadian provinces between 2016 and 2018.MethodsLongitudinal data from the Canadian arm of the 2016 and 2018 ITC Four Country Smoking and Vaping Survey. 1098 non-menthol and 138 menthol smokers were surveyed pre-menthol and post-menthol cigarette bans. Multivariate logistic regression models examined associations between pre-post ban changes in smoking behaviour, including differences between menthol and non-menthol smokers in quit attempts and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
59
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 31 publications
(43 reference statements)
11
59
2
Order By: Relevance
“…The development of tobacco package warning labels and/or multi-media campaigns that reframe these sensory experiences may reduce misperceptions of the potential for reduced risk and undermine the enjoyment that smokers experience when smoking menthol cigarettes, helping these smokers move closer to quitting. In addition, a ban on the use of menthol in tobacco products in Australia would eliminate the source of these sensory experiences and, as has occurred elsewhere [ 51 , 52 ], could be expected to increase quitting behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…The development of tobacco package warning labels and/or multi-media campaigns that reframe these sensory experiences may reduce misperceptions of the potential for reduced risk and undermine the enjoyment that smokers experience when smoking menthol cigarettes, helping these smokers move closer to quitting. In addition, a ban on the use of menthol in tobacco products in Australia would eliminate the source of these sensory experiences and, as has occurred elsewhere [ 51 , 52 ], could be expected to increase quitting behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the public health impact of tobacco flavour bans in the United States, European Union and Canada reported declines in cigarette use, 17 , 18 , 19 , 20 decreased cigarette sales, 17 , 21 and improved cessation outcomes. 17 , 22 , 23 , 24 Two studies have simulated the impact of a menthol cigarette ban in the United States. A 2011 study estimated a 9.7% reduction in smoking prevalence with over 600,000 deaths averted by 2050, assuming 30% quitting and 30% fewer initiations.…”
Section: Introductionmentioning
confidence: 99%
“…As more countries work towards adopting tobacco flavor bans, it is critical to understand how these policies are implemented, ascertain their population-level impact, and identify the regulatory challenges.Initial evaluation of these bans has provided evidence for their positive impact as well as the challenges. Population-level data from the International Tobacco Control (ITC) Surveys in Canada and Europe have demonstrated that banning menthol and other flavors in cigarettes can lead to positive public health outcomes including increased quitting, without significant unintended consequences such as illicit purchasing 4,5 . The menthol cigarette ban in Canada led to 7.5% additional quitting among menthol smokers compared to nonmenthol smokers 4 .…”
mentioning
confidence: 99%
“…Population-level data from the International Tobacco Control (ITC) Surveys in Canada and Europe have demonstrated that banning menthol and other flavors in cigarettes can lead to positive public health outcomes including increased quitting, without significant unintended consequences such as illicit purchasing 4 , 5 . The menthol cigarette ban in Canada led to 7.5% additional quitting among menthol smokers compared to non-menthol smokers 4 . Findings from the EUREST-PLUS ITC Europe Surveys, before and after the flavor ban, but prior to the menthol ban, found a reduction in menthol use 5 as well as other flavors and improved health knowledge and beliefs among menthol smokers.…”
mentioning
confidence: 99%
See 1 more Smart Citation